Physicists Missed These Singularities — They’re in Your Body and Your Bed - Hamidi, Nabil (My University, 2025)
Modern physics encounters singularities at the boundaries of its most successful theories. These regions, predicted by general relativity and implicated in cosmology and black-hole physics, mark domains where curvature, density, and temperature lose definable meaning and predictive laws fail. This article advances the proposition that a singularity represents the absence of any absolute, observable governing authority within nature’s laws. In this sense, the singularity is not an object but a condition of lawlessness, expressible symbolically as 0. Crucially, this absence of final law is not confined to deep space or extreme events; it is observable in ordinary physical systems, within the human body, and across the Earth’s environment, wherever the limits of existing descriptions become visible. Thus, "anarchy" = "singularity" = "0" names the physical boundary at which governing descriptions collapse and cease to operate.